Regulation of neurogenesis by Fgf8a requires Cdc42 signaling and a novel Cdc42 effector protein - Hulstrand, Alissa M. (2013)
Fibroblast Growth Factor (FGF) signaling is required for numerous aspects of neural development, including neural induction, CNS patterning and neurogenesis. The ability of FGFs to activate Ras/MAPK signaling is thought to be critical for these functions. However, it is unlikely that MAPK signaling can fully explain the diversity of responses to FGFs. We have characterized a Cdc42-dependent signaling pathway operating downstream of the Fgf8a splice isoform. We show that a Cdc42 effector 4-like protein (Cdc42ep4-l or Cep4l) has robust neuronal-inducing activity in Xenopus embryos. Furthermore, we find that Cep4l and Cdc42 itself are necessary and sufficient for sensory neurogenesis in vivo. Furthermore, both proteins are involved in Fgf8a-induced neuronal induction, and Cdc42/Cep4l association is promoted specifically by the Fgf8a isoform of Fgf8, but not by Fgf8b, which lacks neuronal inducing activity. Overall, these data suggest a novel role for Cdc42 in an Fgf8a-specific signaling pathway essential for vertebrate neuronal development.